Downsizing prisons: how to reduce crime and end mass incarceration - Jacobson, Michael (New York University Press)
Over two million people are incarcerated in America's prisons and jails, eight times as many since 1975. Mandatory minimum sentencing, parole agencies intent on sending people back to prison, three-strike laws, for-profit prisons, and other changes in the legal system have contributed to this spectacular rise of the general prison population. After overseeing the largest city jail system in the country, Michael Jacobson knows first-hand the inner workings of the corrections system. In Downsizing Prisons , he convincingly argues that mass incarceration will not, as many have claimed, reduce cri